Pendidikan Diniyah: Dinamika TPQ-TQA dan MDT (Awu) dan Sejenisnya Dalam Pengembangan Pendidikan Islam di Indonesia - Ridhatul Husna; Zulmuqim Zulmuqim; Muhammad Zalnur (Jurnal Kawakib, 2022)
This study aims to explore the Al-Quran Education Park (TPQ) is an institution that is engaged in religious activities, as well as the Al-Quran Education Park (TPQ) which should be a very appropriate institution to develop Islamic symbols in terms of deepening read the Qur'an properly and correctly and the madrasa diniyah from a historical perspective. This research is using a library approach. Madrasah Diniyah provide awareness for the Islamic Community about the existence of Religious Education. In its development, it has led to the renewal of Islamic education. In the next phase of Madrasah the diniyah have still received recognition from the government as part of the national education system in Indonesia. It also has a level of education such as basic education which is called madrasah diniyah ula or Awaliyah.